Training Students' Mathematical Literacy Abilities through PISA Standardized Questions with Traditional Games Contexts - Muhammad Afandi; Novi Budi Rahayu S; Surani Surani (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2021)
Indonesia has participated in PISA studies 7 times to measure the mathematical literacy abilities of Indonesian students. However, the results obtained show that Indonesian students are always ranked in bottom 10th. This proves that the mathematical literacy ability of Indonesian students is very low. In response to this, efforts need to be made in improving students' mathematical literacy skills to be better, namely by training students to get used to solving problems that have PISA standards. This study aims to describe how to train students' mathematical literacy skills through PISA standardized questions with the context of Traditional Games. The method used in this research is library research. The results of this study indicate that training students' mathematical literacy skills can be done by accustoming students to solve PISA standardized problems with contexts that are close to students' daily lives namely using the context of Traditional Games.